You wouldn't want to be a Mammoth hunter!: Dangerous Beasts you'd rather not encounter - Malam, John; Antram, David (New York : Scholastic, 2004)
Describes the hazards of human life during the ice age.
Keywords: Cave painting -- Picture Books -- Other Animals